Biodegradation of BTEX (Benzene, Toluene, Ethyl Benzene and Xylene) Compounds by Bacterial Strain under Aerobic Conditions - S. Mary Celin2, Rajni Singh1* and (Journal of Ecobiotechnology, 2010)
Petroleum aromatic hydrocarbons like benzene, toluene, ethyl benzene and xylene, together known as BTEX, share almost the same chemical structure. These aromatic hydrocarbons are widely used in different industries and are released in the environment in abundance thus, polluting the entire ecosystem. Recent bioremedial applications of microorganisms to treat these pollutants have shown significant results. This present work highlight a solvent tolerant bacterial strain Bb5 that degrades BTEX compounds as they all share a common chemical structure. The bacterial strain can tolerate and grow in presence of high concentration of BTEX (10% of toluene, 10% of benzene 2-5% ethyl benzene and 0.5% xylene). Gas chromatography results reveal that the strain is capable of degrading BTEX in different concentrations ranging 100 % in benzene and 80% in toluene within 48 and 72 hours. This property can be used for effluent treatment, solvent waste management. 1Amity Institute of Microbial Biotechnology, Amity University Campus, Sector, 125, Noida - 201301, UP, India 2Centre for fire, Explosives and Environment Safety, Brig. S.K. Majumdar Road, Timarpur, Delhi-110054, India *Corresponding author, Email: rsingh3@amity.edu, Tel: 0120-4392900, Fax: 0120-4392295 Please Cite This Article As: Rajni Singh and S. Mary Celin. 2010. Biodegradation of BTEX (Benzene, Toluene, Ethyl Benzene and Xylene) Compounds by Bacterial Strain under Aerobic Conditions. Journal of Ecobiotechnology 2/4 27-32.